Comparative and phylogenetic analyses based on the complete chloroplast genome of Cornus subg. Syncarpea (Cornaceae) species - Guan, Bicai; Wen, Jianteng; Guo, Hanjing; Liu, Yizhen (Frontiers in Plant Science, 2024)
This study presents a comprehensive analysis of the chloroplast (cp) genomes of Cornus species, including comparative and phylogenetic evaluations, as well as examinations of their genomic structure and composition. The cp genomes exhibit a typical circular quadripartite structure and demonstrated highly similar gene order and genomic structure. The complete cp genome size of the 10 taxa in this study is 156,965bp to 157,383bp, where the length of large single-copy (LSC) region is 86,296bp to 86,691bp, small single-copy (SSC) region is 18,386bp to 18,454bp, and inverted repeat (IR) region is 23,143bp to 26,112bp. A total of 131 genes were found, including, 86 protein-coding genes (PCGs), 8 rRNA genes, and 37 tRNA genes. The mean GC content of the 10 taxa is 38.145%， while in LSC region is 36.396%, SSC region is 32.372%, and IR region is 43.076%. Despite the relatively conserved nature of the cp genome within the species of Cornus, 25-31 simple sequence repeats (SSRs) were identified of the 10 taxa in our study, respectively. The SSRs were found to be distributed in the LSC, SSC, and IR regions in Cornus hongkongensis subsp. hongkongensis, C. hongkongensis subsp. elegans, C. hongkongensis subsp. gigantea, and C. hongkongensis subsp. tonkinensis, while the SSR was not found in the IR region of the other six taxa. Thus, whole cp genomics is a valuable tool for species identification, taxonomic clarification, and genomic evolutionary analysis. Furthermore, our findings reveal that C. hongkongensis and C. hongkongensis subsp. gigantea, along with C. kousa and C. elliptica, form sister groups. Notably, C. hongkongensis subsp. ferruginea and C. hongkongensis subsp. melanotricha did not exhibit affinity with C. hongkongensis subsp. hongkongensis. Our study furnishes essential data for further research on their classification and provides novel insights into the relationship within Cornus subg. Syncarpea.